PENGARUH LITERASI KEUANGAN DAN PERILAKU KEUANGAN TERHADAP MINAT INVESTASI MAHASISWA FEB UNIVERSITAS ISLAM MALANG - Nadia B Tehupelasuri; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to analyze and measure the effect of financial literacy and financial behavior on student / female student investment interest. The type of research used is quantitative research with explanatory research methods. Types and sources of data used are primary data, namely data collected and processed by themselves from the object. The population in this study were 261 students with the sample technique used was purposive random sampling using the Slovin formula. Data were collected using a questionnaire method from 65 students / female students as samples in this study. The data technique used in this research is descriptive analysis, instrument test, classical assumption test, multiple linear regression test, F test, t test, determination coefficient test with the help of SPSS version 16 software program. These results indicate that financial literacy and financial behavior have an effect. significant positive on investment interest.Keywords: Financial Literacy, Financial Behavior and Investment Interest